The development of the modern state : a sociological introduction - Poggi, Gianfranco (London, United Kingdom : Hutchinson & Co. (Publishers) Ltd., 1978)
Sociologists in western countries have of late become more and more concerned with various problems relating centrally to the notion of the state.
I. Introduction: the business of rule -- II. The feudal system of rule -- III. The standestaat -- IV. The absolutist system of rule -- V. The nineteenth-century constitutional state -- VI. State and society under liberalism and after.
Includes index.
Keywords: CONSTITUTIONAL -- HISTORY